Optimization and modeling of teff-maize-rice based formulation by simplex lattice mixture design for the preparation of brighter and acceptable injera - Zewdu Cherie; Gregory R. Ziegler; Habtamu Fekadu Gemede; Ashagrie Zewdu Woldegiorgis (Cogent Food & Agriculture, 2018)
Simplex lattice mixture design was utilized to optimize a brighter and acceptable injera (Ethiopian staple bread). Fourteen formulations of injera were produced from constrained blends of teff (70–100%), maize (0–30%) and rice (0–30%). Investigated responses were proximate, mineral, sensory and lightness (L* value). Nutritional values (g/100 g) ranged from 59.3 to 62.8 (moisture), 1.74 to 2.76 (ash), 11.5 to 14.7 (protein), 2.1 to 2.6 (fat), 3.91 to 5.2 (fiber) and 75.9 to79.4 (carbohydrate). Minerals (mg/100 g) varied from Fe: 17.7 to 25.1, Zn: 1.62–2.10, and Ca: 25.9 to 51.1. Sensory scores for color, taste, texture, number of eyes, eye size, eye distribution, top & bottom surface and overall acceptability were 5.63–7.72, 5.22–6.21, 4.83–7.70, 6.02–7.27, 4.12–5.82, 5.42–6.93, 5.97–7.02, and 5.32–7.25, respectively, while the L* value ranged from 54.9 to 63.1. Optimum formulations of injera in terms of color, overall acceptability and L* value consisted of 70% teff, 0% maize and 30% rice with a desirability of 0.909. Numerical optimization also indicated that better sensory, proximate and mineral qualities are directly related with the proportion of rice; maize and teff, respectively.